2005
DOI: 10.1163/22941932-90000128
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Wood Anatomical Properties of Tumorous Wood in a Turkish White Oak (Quercus Robur Subsp. Robur)

Abstract: Chemical and anatomical properties of tumorous and normal wood of Quercus robur L. subsp. robur were compared. Tumorous growth appeared as a result of topping stress. Orientation of cells was severely disrupted in the affected wood. In cross section, aspects of cells changed abruptly from transverse to longitudinal, and in tangential section all wood elements appeared to turn around each other like a fingerprint. Vessel elements and fibres of affected wood were shorter than those of healthy wood. The vessels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
1
7
0
4
Order By: Relevance
“…The between-tree comparison of normal and abnormal wood in this experiment showed similiar tendencies (in hemicellulose, ethanol-toluene, hot-water solubles, and solubility in NaOH 1% rates) as a previous report of tumorous wood in Quercus robur (Gulsoy et al 2005) and Erica arborea in extractive and ash contents (Tsoumis et al 1988). Rickey et al (1974), working with Picea sitchensis, also noted that hemicellulose content in tumorous wood was higher than in normal wood but that other parameters were even.…”
Section: Chemical Properties Of Tumorous/insect Attacked Woodsupporting
confidence: 80%
See 1 more Smart Citation
“…The between-tree comparison of normal and abnormal wood in this experiment showed similiar tendencies (in hemicellulose, ethanol-toluene, hot-water solubles, and solubility in NaOH 1% rates) as a previous report of tumorous wood in Quercus robur (Gulsoy et al 2005) and Erica arborea in extractive and ash contents (Tsoumis et al 1988). Rickey et al (1974), working with Picea sitchensis, also noted that hemicellulose content in tumorous wood was higher than in normal wood but that other parameters were even.…”
Section: Chemical Properties Of Tumorous/insect Attacked Woodsupporting
confidence: 80%
“…No study has been conducted so far, however, to examine the actual properties of this kind of wood. In other species, the chemical properties of tumorous wood for which the causes are unknown have been investigated (Rickey et al 1974;Tsoumis et al 1988;Gulsoy et al 2005). Those results showed that some abnormal tree growths have different chemical properties compared to normal areas.…”
Section: Introductionmentioning
confidence: 99%
“…La madera con tumor tiene todos los elementos celulares que la madera sana (Chattaway, 1958), aunque presenta una estructura anatómica diferente (El Mouridi et al, 2011). En otras palabras, la orientación de las células de la madera con tumor está desorganizada (Gülsoy et al, 2005), dispuesta en forma de contorta (Paula, Naulin, Arce, Galaz y Pausas, 2016). Por todo ello, las propiedades mecánicas de la madera con tumor son notoriamente diferentes de la madera sana (Rosero, Hernández y Riedl, 2017).…”
Section: B Módulo De Ruptura (Mor) Y Módulo De Elasticidad (Moe)unclassified
“…Seperti yang terjadi pada batang Fraxinus sp. yang terserang kanker, terdapat modifikasi serat yang berombak; sedangkan pada tanaman Quercus robur yang terserang tumor terjadi perubahan susunan sel pada batang, serat memiliki panjang lebih pendek dari sel batang normal (Gülsoy, Eroĝlu, & Merev, 2005). Menurut Rukhama (2014), serabut pada kayu yang terserang karat tumor lebih pipih dan panjang dari kayu sehat, dan ini diduga karena pengaruh hormon auksin Hasil analis varians juga tidak menunjukkan terdapatnya perbedaan yang nyata pada diameter serat antar sampel pohon Wamena dan Solomon (db=1, ms= 24,04, Fpr=0,323), meskipun rata-rata diameter serat Solomon (36,44 µm) lebih tinggi dari batang Wamena (33,61 µm).…”
Section: Proporsi Sel Xilemunclassified